Precision and safety advantages of ultrasound-guided nerve blocks in geriatric anesthesia: current status and future prospects - Lin, Xiao-yin; Yang, Ya-mei; Liu, Yang; Dang, Qing-qing; Zhang, Kan (Frontiers in Medicine, 2025)
Ultrasound-guided regional anesthesia (UGRA) has emerged as a pivotal advancement in geriatric anesthesia, significantly enhancing procedural precision and patient safety through dynamic, real-time sonographic visualization. This technology overcomes critical limitations of conventional landmark-based techniques by enabling accurate needle navigation and localized anesthetic delivery, thereby improving block success rates while reducing volume requirements and systemic exposure. In elderly populations, characterized by heightened vulnerability to pharmacological adverse events and perioperative complications, UGRA facilitates opioid-minimized analgesia, attenuates neuroinflammatory responses, and lowers the incidence of delirium and cognitive dysfunction. Its alignment with enhanced recovery after surgery (ERAS) protocols further promotes early mobilization and functional recovery. Despite existing challenges in technical training and resource allocation, ongoing innovations in imaging artificial intelligence, sustained-release local anesthetics, and personalized protocols hold substantial potential to broaden its applications. Future integration of UGRA into perioperative care necessitates standardized competency-based training and rigorously designed multicenter clinical trials to consolidate its role in improving outcomes for the aging surgical population.